Using ‘soft’ and ‘hard’ social impact indicators to understand societal change caused by mining: a Western Australia case study - Petrova, S.; Marinova, Dora (2015)
© 2015, © 2014 IAIA. The paper explores the qualitative changes occurring in the local social landscape as a result of mining. Building on Colantonio's social sustainability assessment framework, we argue that there are three thematic areas (related to demographics, social capital and well-being) which identify change generally and specifically caused by mining. By studying the social impacts of mining, we examine both ‘hard’ themes around quantifiable indicators and ‘soft’ themes which deal with less tangible community characteristics and values. The analysis of the Western Australian Boddington case study demonstrates that such an approach can generate important insights about a community's nature and potential capabilities to cope and respond to change. We argue that if social impact assessment is to be used as a development tool, which is a tool that facilitates development, there is need to understand those aspects of the social environment that impact positively and/or negatively its demographic, quality and operational attributes as they influence the overall capacity of communities to maintain and enhance their long-term functioning.